2016
DOI: 10.1016/j.jtos.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Punctal Occlusion on Clinical Signs and Symptoms and on Tear Cytokine Levels in Patients with Dry Eye

Abstract: Punctal plug occlusion provided symptomatic relief and reduced fluorescein staining in all except the inferior zone. However, insertion of punctal plugs had minimal effect on tear cytokines and MMP-9 levels, suggesting a need for earlier treatment with anti-inflammatory agents for management of dry eye disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 37 publications
0
41
0
1
Order By: Relevance
“…However, artificial tears do not significantly reduce MMP-9 levels,31,32 prevent underlying inflammation, or reverse conjunctival squamous metaplasia in chronic dry eye 31. Tong et al showed that MMP-9 levels are unchanged 3 weeks after punctal occlusion 33. Punctal occlusion should be reserved for patients without ocular surface inflammation or performed after the inflammation is under control 34,35…”
Section: Discussionmentioning
confidence: 99%
“…However, artificial tears do not significantly reduce MMP-9 levels,31,32 prevent underlying inflammation, or reverse conjunctival squamous metaplasia in chronic dry eye 31. Tong et al showed that MMP-9 levels are unchanged 3 weeks after punctal occlusion 33. Punctal occlusion should be reserved for patients without ocular surface inflammation or performed after the inflammation is under control 34,35…”
Section: Discussionmentioning
confidence: 99%
“…As can be observed in the Tables , a wide range of concentrations has been observed for these cytokines. For example, while tears from DED patients tested for IL-8 showed higher mean values for IL-8 compared to normals (Table 6), the reported concentrations ranged from 74 + 55 pg/mL 65 to 6518.3 + 4509.7 pg/mL 66 for DED and from 176 + 72 pg/mL 67 to 1150 + 50 pg/mL in normals. 68 While some of the variability, as with IC studies (Table 2), may be due to biologic variations, the technique used is likely an issue as well.…”
Section: Biomarkers Of Inflammationmentioning
confidence: 98%
“…They can be classified into temporary short duration plugs that are usually made of animal collagen and last for 4–14 days, and temporary extended duration plugs that last from 2 to 6 months and they are made of different materials that include silicone, hydrogel, polydioxanone and acrylic. The temporary extended duration punctal plugs are the type used following refractive surgery [1013]. …”
Section: Introductionmentioning
confidence: 99%